PENGARUH KETERLAMBATAN KEWAJIBAN MEMBAYAR PREMI TERHADAP KINERJA KEUANGAN PERUSAHAAN ASURANSI JIWA BERSAMA (AJB) BUMIPUTERA 1912 CABANG KESAWAN - Dwi Novita Anggraini; ova novi irama (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2019)
This study entitled "The Influence of Liability of Paying Premium To Financial Performance of Joint Life Insurance (AJB) Bumiputera 1912 Branch of Kesawan". The purpose of this study is to determine how much influence the delay in paying the premium to the performance of life insurance company paying (AJB) bumiputera 1912 branch kesawan. Research method: observation, documentation technique and quantitative descriptive approach. Population and sample: The population in this study is the report of joint life insurance financial report (AJB) bumiputera 1912 branch kesawan and sample in this study is the income statement and the monthly balance of the period 2014-2016 so that the observation data obtained amounted to 36 samples. Method of analysis: Descriptive analysis, Simple linear regression analysis, Coefficient of determination. Result of hypothesis testing done, got significance value equal to 0,002 and t count 3,333 delay pay premium (X). Based on the results of the analysis conducted, as for the conclusion of this study that the delay of paying the premium affects the financial performance of a joint life insurance company (AJB) bumiputera 1912 branch kesawan. Keywords: Late, Premium Payment and Financial Performance